THE IMPACT OF ALOE VERA POWDER ON THE CHARACTERISTIC OF REDUCED FAT MAYONNAISE DURING STORAGE PERIOD - Sylvani, Mozza Indira; Evanuarini, Herly; Rahayu, Premy Puspitawati (Fakultas Peternakan, Universitas Padjadjaran, 2025)
Steps considered in the creation of healthy functional foods are reducing the fat content in low-fat mayonnaise (RFM). During storage, RFM is susceptible to emulsion instability, lipid oxidation, and general quality decline. Natural additives are needed to improve the quality of mayonnaise, including antioxidants, maintaining emulsion stability, one of which is aloe vera powder (AVP). This study aims to determine the effect of AVP use on days 0, 5, 10, and 15, on the physicochemical and organoleptic properties of RFM during storage. This study used the addition of aloe vera powder to low-fat mayonnaise production. The study was conducted with four treatments and six replications, using a completely randomized design (CRD) through a laboratory experimental approach. The FTIR technique was used to examine AVP to identify functional groups that affect the quality of RFM. The physicochemical and organoleptic qualities of RFM were much better by adding 6% AVP to RFM for 0, 5, 10, and 15 days (P <0.01). In terms of physicochemical and organoleptic quality, storage of mayonnaise with AVP in RFM for up to 15 days still shows good properties.